2019
DOI: 10.1097/sla.0000000000002862
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Matched Comparison of Transanal and Robotic Total Mesorectal Excision for Mid and Low-rectal Adenocarcinoma

Abstract: High-quality TME for patients with rectal adenocarcinoma of the mid and low rectum can be equally achieved by transanal or robotic approaches in skilled hands, but attention should be paid to the distal margin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 48 publications
1
47
2
1
Order By: Relevance
“…After removing duplicates, 739 publications were further reviewed. Further screening found that 23 studies [15][16][17][18][19][20][21][22][24][25][26][27][28][29][30][31][32][33][34][35][36]47,48 met the predefined inclusion criteria. The selection process is reported in Figure 2.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing duplicates, 739 publications were further reviewed. Further screening found that 23 studies [15][16][17][18][19][20][21][22][24][25][26][27][28][29][30][31][32][33][34][35][36]47,48 met the predefined inclusion criteria. The selection process is reported in Figure 2.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…Among the included studies, eight were prospective, 24,25,28,29,32,34,35,48 and 15 retrospective. [15][16][17][18][19][20][21][22]26,27,30,31,33,36,47 F I G U R E 1 Network geometry for studies reporting A, complete mesorectum excision; B, near complete mesorectum excision; C, incomplete mesorectum; D, radial margin involvement; E, lymph node harvest; F, local recurrence; G, distal recurrence; H, overall complication rate; I, anastomotic leak; L, wound infection; M, urinary dysfunction; N, bowel obstruction; O, reoperation; and P, 30-day mortality. lapTME, laparoscopic TME; roTME, robotic-assisted TME; taTME, transanal TME; TME, total mesorectal excision…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…According to a recent paper in the study by Lee et al comparing the outcomes of robotic and taTME for mid-and low-rectal cancer (! 10 cm from the anal verge) using coarsened exact matching, short-term postoperative outcomes and pathological outcomes were closely comparable ( Table 2) 59) . It should be noted that distal margin tumor involvement was observed more frequently in the taTME group (1.8% vs. 0.3%; P = 0.051) as opposed to the robotic group, despite the longer length to distal margin (16.9 mm vs. 15.1 mm; P = 0.097).…”
Section: Future Prospectsmentioning
confidence: 83%
“…Several retrospective studies comparing robotic surgery and taTME for rectal cancer have revealed that they are equivalent as per short-term outcomes and/or histopathological outcomes 59,60) . According to a recent paper in the study by Lee et al comparing the outcomes of robotic and taTME for mid-and low-rectal cancer (!…”
Section: Future Prospectsmentioning
confidence: 99%
“…Proponents of taTME believe that this is the best approach for rectal dissection, as this technique offers great access to distal 1/3 rectal dissection, a good view of the pelvic anatomy, the ability to define the distal resection margin and potential for double purse-string anastomosis. A multicentre study comparing robotic TME to taTME has found that high quality TME can be achieved by both robotic and transanal approaches in skilled hands [45] . However, long term data on oncological and functional outcomes of taTME are yet to be established.…”
Section: Ability To Perform An Advanced Mis Procedures Roboticallymentioning
confidence: 99%